Enablers and barriers in accessing sexual and reproductive health services among visually impaired women in the Ashanti and Brong Ahafo Regions of Ghana. Issue 54 (8th November 2018) - Badu, Eric; Gyamfi, Naomi; Opoku, Maxwell Preprah; Mprah, Wisdom Kwadwo; Edusei, Anthony Kweku
Abstract: The need to improve the sexual and reproductive health (SRH) and rights of women with disabilities is increasingly acknowledged. Unfortunately, women with disabilities in low- and middle-income settings, including Ghana, face several barriers (including structural, financial, physical, social and attitudinal) to accessing SRH services and care. This paper explores the enablers and barriers to accessing SRH services and care among visually impaired women in the Ashanti and Brong Ahafo Regions of Ghana. Qualitative data from in-depth interviews and focus group discussions were collected from 21 visually impaired women, selected through purposive and snowballing sampling techniques. Thematic analysis was used to develop codes, and data were further grouped into emerging themes. The barriers to accessing SRH services and care were financial difficulties and lack of preferential treatment. The enablers which facilitated access to SRH services and care were the support provided by caregivers and friendly relationships with health providers. To address these challenges and promote access, SRH related policies, services and programmes should be inclusive of the needs of visually impaired women, and measures to remove financial challenges to service utilisation and foster positive relationships with health workers, church and community members should be adopted.